Beneficial effect and mechanism of walnut oligopeptide on Lactobacillus plantarum Z7. Issue 2 (8th January 2021) - Ding, Ting; Li, Yong
Abstract: Prebiotics can stimulate the growth and activity of probiotics and have a variety of physiological functions. However, the study of walnut oligopeptides as prebiotics to promote probiotics is rarely reported. Therefore, in order to explore the beneficial effect of walnut oligopeptide (WOPs) on Lactobacillus plantarum Z7, WOPs was added to the medium of L. plantarum Z7, and the utilization of WOPs, the effect of WOPs on the biofilm, extracellular polymeric substances, and bacterial death were explored. The results showed that the growth‐promoting effect was strengthened with the increasing concentrations of WOPs. The content of bacterial biofilm and EPS increased significantly, and the number of dead bacteria decreased. The beneficial effect of WOPs was probably because that it enhanced the secretion of biofilm which was regulated by bacterial quorum sensing system and promoted the ability of bacteria to resist the adverse environment, thus promoting the growth and reproduction of bacteria. Abstract : Walnut oligopeptide (WOPs) promoted the growth and reproduction of bacteria and increased the secretion of bacterial biofilm and EPS, which make WOPs to be a new and potential prebiotic to promote the growth and quality nutritional value of related products.